Chili Plants Soil Fertility Monitoring System Based on Internet of Things (IoT) - Wahyu Prawoto; Anton Yudhana (Buletin Ilmiah Sarjana Teknik Elektro, 2022)
Soil fertility is one of the main factors in cultivating chili peppers. Variables that need to be considered to support chili growth include soil temperature and pH. This study aims to monitor soil fertility using the DS18B20 temperature sensor and an Internet of Things (IoT)-based soil pH sensor combined with the Geographical Information System (GIS) algorithm. Ituses parameters of temperature values and soil pH values with geographic readings via GIS. The DS18B20 temperature sensor values and ground pH sensor are processed on the ESP8266 NodeMCU then displayed on a 20x4 LCD and sent to the ThingSpeak website in real time. Soil fertility testing is carried out in the morning and evening by comparing the measurement results of the DS18B20 temperature sensor and soil pH sensor with a standard tool, namely the 4in1Soil Survey Instrument. The results of soil fertility testing using the DS18B20 temperature sensor and soil pH sensor conducted in the morning obtained a temperature accuracy of 95.36% and a pH accuracy of 95.96%. Meanwhile, the results carried out in the afternoon obtained a temperature accuracy of 94.36% and a pH accuracy of 89.96%. The implementation of GIS in this study succeeded in mapping the fertility of good and bad soils.